Das Ende der Postdemokratie, den Pessimismus überwinden. - Mullis, Daniel (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
In recent years, political and social conditions have changed dramatically. Many analyses help to capture these dynamics. However, they produce political pessimism: on the one hand there is the image of regression and on the other, a direct link is made between socio-economic decline and the rise of the far-right. To counter these aspects, this article argues that current political events are to be understood less as ‘regression’ but rather as a moment of movement and the return of deep political struggles. Referring to Jacques Ranciere’s political thought, the current conditions can be captured as the ‘end of post-democracy’. This approach changes the perspective on current social dynamics in a productive way. It allows for an emphasis on movement and the recognition of the windows of opportunity for emancipatory struggles.